Using response surface methodology to optimize foam drying conditions related to drying rate and B-carotene concentration of orange-fleshed sweet potato powder - Tran Ngoc Giau; Nguyen Chi Dung; Hong Van Hao; Vo Quoc Tien; Nguyen Minh Thuy; Ngo Van Tai; Vo Quang Minh (My University, 2024)
Response surface methodology and Box-Behnken design (3 factors and 3 levels) were performed to optimize the effects of different egg albumin contents (5-15%), xanthan gum (0.1-0.5%) and drying temperature (50-70oC). Drying rate and β-carotene content are indicators observed through 18 experimental runs and 6 repetitions at the center point. Finally, the physical properties such as color, water solubility index, water absorption index and rehydration ratio together with moisture content, water activity and microstructural of OFSP powder were analysed. The total polyphenol content (TPC), DPPH scavenging activity and β -carotene were analysed. Research results revealed that the optimal egg albumin concentration, xanthan gum concentration and drying temperature of 10.73%, 0.33% and 65.48oC, respectively as foam-mat drying parameters were recorded. From those optimal parameters, the optimal values of drying rate and β-carotene were determined to be 2.34 g water/g dry matter/min (maximize) and 51.82 µg/g (maximize), respectively. Foam-mat dried powder contained low moisture content and water activity, 4.15% and 0.343, respectively, along with water solubility index, water absorption index and rehydration ratio were respectively determined to be 45.87%, 2.36% and 3.97. The color of foam-mat dried OFSP powder was evaluated. According to the ﬁndings, the content of β-carotene (48.61±0.5 μg/g) and TPC (2.24±0.04 mgGAE/g) along with antioxidant activity (57.43±1.2%) of OFSP powder products were also determined. SEM analysis of OFSP powder particles at different magnifications showed that they have irregular surface morphology and flake-like structures, different from the structure of powder particles dried by convection drying method, the surface is quite smooth and the structure is intact.
Keywords: Carotene; Food Drying and Modeling